Public supervision of audit. Theory vs practice - О. REDKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The article conducts a comparative analysis of the theory and practice of the organization of public supervision in the world and in Ukraine. It is concluded that there is a partial discrepancy between the principles of public supervision and the practice of its implementation. It is stated that supervision is only in words public, but in practice - state. Ukraine is on the path of full repetition of foreign experience in the field of public control over the audit. It is concluded that the concentration of power over the audit profession in a state body that is not subordinate to anyone and is not accountable in the state itself.